A computational strategy for the search of regulatory small RNAs inActinobacillus pleuropneumoniae - Rossi,CC; Bosse,JT; Li,Y; Witney,AA; Gould,KA; Langford,PR; Bazzolli,DMS (RNA, 2016)
Bacterial regulatory small RNAs (sRNAs) play important roles in gene regulation and arefrequently connected to the expression of virulence factors in diverse bacteria. Only a fewsRNAs have been described for Pasteurellaceae pathogens and no sRNA has yet beendescribed for Actinobacillus pleuropneumoniae, the causative agent of porcinepleuropneumonia, responsible for considerable losses in the swine industry. To search forsRNAs in A. pleuropneumoniae, we developed a pipeline for the computational analysis ofthe bacterial genome by using four algorithms with different approaches, followed byexperimental validation. The coding strand and expression of 17 out of 23 RNA candidateswere confirmed by Northern blotting, RT-PCR and RNA sequencing. Among them, two arelikely riboswitches, three are housekeeping regulatory RNAs, two are the widely studiedGcvB and 6S sRNAs, and ten are putative novel trans-acting sRNAs, never before describedfor any bacteria. The latter group has several potential mRNAs targets, many of which areinvolved with virulence, stress resistance or metabolism, and connect the sRNAs in acomplex gene regulatory network. The sRNAs identified are well conserved among thePasteurellaceae that are evolutionarily closer to A. pleuropneumoniae and/or share the samehost. Our results show that the combination of newly developed computational programs canbe successfully utilized for the discovery of novel sRNAs and indicate an intricate system ofgene regulation through sRNAs in A. pleuropneumoniae and in other Pasteurellaceae, thusproviding clues for novel aspects of virulence that will be explored in further studies.